2022
DOI: 10.1038/s41598-022-17848-y
|View full text |Cite
|
Sign up to set email alerts
|

Fragment size and dynamics of EGFR-mutated tumor-derived DNA provide prognostic information regarding EGFR-TKI efficacy in patients with EGFR-mutated NSCLC

Abstract: Circulating tumor DNA (ctDNA)-based next-generation sequencing (NGS) is a complementary and alternative test to tissue-based NGS. We performed NGS analysis of ctDNA samples collected from patients with EGFR-mutated non-small cell lung cancer (NSCLC) who received osimertinib; the samples were collected after second-line treatment, before osimertinib treatment, one week and one month after osimertinib treatment, and at the time of resistance formation. We examinedthe correlation with osimertinib efficacy. From J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Tumor clonal changes can predict the efficacy of EGFR-TKIs and whether patients will develop drug resistance [ [29] , [30] , [31] ]. These genetic clonal changes may include EGFR mutations, mutations in other signaling pathway genes, alterations in cell cycle regulatory genes, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor clonal changes can predict the efficacy of EGFR-TKIs and whether patients will develop drug resistance [ [29] , [30] , [31] ]. These genetic clonal changes may include EGFR mutations, mutations in other signaling pathway genes, alterations in cell cycle regulatory genes, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that insufficient tumor biopsy samples that yield inconclusive molecular results occur in 8-26% of patients [38]. To this significant problem, EGFR evaluation using ctDNA represents a clinically useful alternative [39]. The diagnostic accuracy of ctDNA analysis in detecting EGFR mutations in NSCLC patients' plasma has been confirmed in several studies, where a high level of concordance compared to traditional tissue genotyping has been observed [40].…”
Section: Ctdna In the Prognosis Of Egfr-mutant Nsclcmentioning
confidence: 98%
“…This 'liquid biopsy' can characterize a tumor in a manner comparable to a tissue biopsy and holds significant promise for orchestrating approaches for early detection, diagnosis, assessment of minimal residual disease, genotyping tumors, and tracking therapeutic response and resistance (4)(5)(6)(7)(8). Several actionable mutations in genes with diagnostic and prognostic significance, such as EGFR for lung cancer, and KRAS and BRAF for colorectal cancer have been well-studied from ctDNA extracted from peripheral blood samples (9)(10)(11)(12). However, many limitations hold liquid biopsy back from its full potential, and tissue biopsy remains the standard of care in current clinical oncology practice (2, 3, 7, 8).…”
Section: Introductionmentioning
confidence: 99%